Evidence for Prosody in Silent Reading. Issue 2 (18th December 2013) - Gross, Jennifer; Millett, Amanda L.; Bartek, Brian; Bredell, Kyle Hampton; Winegard, Bo
Abstract English speakers and expressive readers emphasize new content in an ongoing discourse. Do silent readers emphasize new content in their inner voice? Because the inner voice cannot be directly observed, we borrowed the cap‐emphasis technique (e.g., "toMAYto") from the pronunciation guides of dictionaries to elicit prosodic emphasis. Extrapolating from linguistic theories of focus prosody in spoken English, we predicted and found that silent readers in experiment 1 preferred cap‐emphasized, newsworthy content ("James stole the BRACELET") when the just‐read story left them wondering what was stolen (compared with control trials). Readers preferred "JAMES stole the bracelet" when left wondering who the thief was. Experiment 2 generalized our findings to newsworthy function words and to a new behavioral measure, reaction time. As predicted, "He CAN" was judged more quickly and accurately following "Can he swim, " whereas "HE can" was judged more quickly and accurately following "Who can swim?" Our results suggest that readers engage focus prosody when they read silently.